Proceedings of SPE Formation Damage Control Conference 1998
DOI: 10.2523/39437-ms
|View full text |Cite
|
Sign up to set email alerts
|

New Criteria for Gravel and Screen Selection for Sand Control

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractGuidelines for sand control completion technique and gravel size selection are presented. These new criteria are based primarily on reservoir sand size distribution. Emphasis is on formations with very high fines content and a wide distribution of grain sizes. Upon failure and/or particle movement, these formations can exhibit very high skins and reduced production capacity with traditional control methods. Guidelines are also discussed for formations with li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…Установка гравийных фильтров. Закачивание крупнозернистого кварцевого песка помогает сдерживать мехпримеси на скважинах с открытым забоем [35,36,[37][38][39][40].…”
Section: исследование методов борьбы с пескопроявлениями и техник наunclassified
“…Установка гравийных фильтров. Закачивание крупнозернистого кварцевого песка помогает сдерживать мехпримеси на скважинах с открытым забоем [35,36,[37][38][39][40].…”
Section: исследование методов борьбы с пескопроявлениями и техник наunclassified
“…Other indicators that impact the sandcontrol design have been suggested by George King et al in SPE 39437. 1 The King et al approach suggests evaluating a sorting coefficient and percentage of fines (sub 44 micron particles) in the formation sample to assist in selecting the sandface completion. Sorting coefficient (defined as D10/D95) gives a broader evaluation of the sand-size distribution, and in the F13-6, core was in the range of 2.5 to 130, further confirming that the Shallow Clastics formation is composed of highly nonuniform sand-grain sizes.…”
Section: Formation Sand Size Distribution and Impact On Sand Controlmentioning
confidence: 99%
“…But the gravel packing is used in concert with other screen in oil field which is fit for the formation of high fine particles content. Such as, Tiffin (Tiffin et al 1998(Tiffin et al , 2003 introduced two new parameters in sand control with the sand particle size distribution: sorting characteristics (SC = d10/d95) and fine particles (the quality percentage of \45 lm particles), and the gravel packing completion was used in the formation of high fine particles content. Mohamad et al (2008) published an article in the JPT which showed fine particles (\45 lm) content with 35 %.…”
Section: Introductionmentioning
confidence: 99%